A Procedure for Attachment of Gold Chain for Traction of Impacted Teeth - Kaan Sheung K; Goh GekKiow (Sciendo, 1992)
There is a need to improve the strength of the attachment of the gold chain to impacted teeth. Dislodgement of the gold chain requires a second surgery for reattachment. Failures have been observed to occur at two interfaces. The authors have devised a method of attaching the gold chain to the mesh pad securely, by ligating them together. This article describes the method and discusses other factors which enhance the retention of the gold chain to the impacted tooth.